A LESS INVASIVE METHOD OF REDUCING THE INCIDENCE OF POST-ENDOSCOPIC RETROGRADE CHOLANGIOPANCREATOGRAPHY PANCREATITIS: INTRAVENOUS DICLOFENAC SODIUM VERSUS PLACEBO - Chik, Ian; Jarmin, Razman; Ariffin, Affirul; Othman, Hairol; Zuhdi, Zamri; Azman, Azlanudin; Mahmood, Nik Ritza Kosai Nik (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The purpose of this study is to reduce the incidence of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) by the administration of intravenous (IV) diclofenac sodium. Methods: This is a prospective, randomized, double-blinded control study. This study was performed in the hepatobiliary unit of general surgery department in University Kebangsaan Malaysia Medical Centre (UKMMC) from May 2015 to May 2016. A total of 128 patients were enrolled in this study. 59 patients were randomized into the treatment arm, while 63 were randomized into the control group. Patients were randomized by envelope system, and patients in the treatment arm received 75 mg of diclofenac sodium intravenously, within 30 min of ERCP commencement. Both groups were observed for PEP post-ERCP and their pain score recorded. Patients’ demographic data were also observed. Results: A total of 122 patients were included in the study, with 59 patients randomized into the treatment arm and 63 into the placebo arm. There was an increase of 7.6% PEP rates in the placebo group (12.7% vs. 5.1% in the treatment arm). However, this was not statistically significant (p=0.142) Conclusion: This study shows that IV diclofenac sodium can decrease PEP but is not statistically significant.